Weapon performance drives weapon evolution - Emberts, Zachary (Proc Biol Sci, 2021)
Many sexually selected traits function as weapons, and these weapons can be incredibly diverse. However, the factors underlying weapon diversity among species remain poorly understood, and a fundamental hypothesis to explain this diversity remains untested. Although weapons can serve multiple functions, an undeniably important function is their role in fights. Thus, a crucial hypothesis is that weapon diversification is driven by the evolution of weapon modifications that provide an advantage in combat (e.g. causing more damage). Here, we test this fighting-advantage hypothesis using data from 17 species of coreid bugs. We utilize the fact that male–male combat in coreids often results in detectable damage, allowing us to link different weapon morphologies to different levels of damage among species. We find that certain weapon morphologies inflict much more damage than others, strongly supporting the fighting-advantage hypothesis. Moreover, very different weapon morphologies can inflict similarly severe amounts of damage, leading to a weapon performance landscape with multiple performance peaks. This multi-peak pattern could potentially drive different lineages towards divergent weapon forms, further increasing weapon diversity among species. Overall, our results may help explain how sexually selected weapons have evolved into the diversity of forms seen today.